Epidemiological Surveillance of Congenital Defects in the Cienfuegos Province - Taimí Barrueta Ordóñez; Diana Ferriol Dorticós; Mónica Marín García; Leydi María Sosa Águila; María Antonia Ocaña Gil (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: congenital defects are among the leading causes of death in children under one year of age. They constitute a problem for the individual, the family, and society. In Cuba they are the leading cause of death in children under one year of age and in Cienfuegos they rank third. Objective: to describe the most frequent congenital defects presented in the Cienfuegos province between the years 2011 and 2018 and to determine the prevalence at birth, adjusted frequency and trend. Methods: a descriptive, cross-sectional study of the most frequent congenital defects in the Cienfuegos province was carried out, in the period 2011-2018. The universe of 330 live-born children with congenital defects diagnosis and 286 voluntary terminations of pregnancy. The results were presented in data tables or graphs as it was more feasible to display the information. The variables analyzed were: prevalence at birth per year of the occurrence of congenital defects, adjusted frequency, and the most frequent major anomalies in the province. Data analysis was carried out by collecting information in a database for which the model of the congenital malformations Cuban registry and the Cuban congenital malformations prenatal registry was used. The prevalence at birth and the adjusted frequency were determined, as well as the trend in the occurrence of some congenital defects in the province. The results were presented in graphs and data tables as it was more feasible to show the information. Results: down syndrome, hydrocephalus and open anterior wall defects were the ones that most frequently occurred in the Cienfuegos population, with a decreasing trend in the appearance of anomalies such as: esophageal atresia, transposition of the great vessels, among others. Conclusions: down syndrome, hydrocephalus and open anterior wall defects were the congenital defects that most frequently occurred in the pediatric population in Cienfuegos.